First results of a European multi-center registry of patients with anorectal malformations - Baauw, Ivo de; Wijers, Charlotte H. W.; Schmiedeke, Eberhard; Holland-Cunz, Stefan; Gamba, Piergiorgio; Marcelis, Carlo L. M.; Reutter, Heiko; Aminoff, Dalia; Schipper, Muriel; Schwarzer, Nicole; Grasshoff-Derr, Sabine; Midrio, Paola; et al. (Journal of pediatric surgery, 2013)
Background - The European consortium on anorectal malformations (ARM-NET) was established to improve the health care of patients and to identify genetic and environmental risk factors. The aim of the present study was to present the first results on clinical data of a large European cohort of ARM patients based on our registry. - Methods - In 2010, the registry was established including patient characteristics and data on diagnosis, surgical therapy, and outcome regarding complications. Patients born between 2007 and 2012 were retrospectively added. A descriptive analysis of this cohort was performed. - Results - Two hundred and three ARM patients were included. Syndromes or chromosomal abnormalities were present in 9%. Perineal fistulas were seen most in boys (42%) and girls (29%). Rare forms of ARM were found in 4% of the male and in 14% of the female patients. Forty-five percent of the patients had additional urogenital abnormalities. However, 32% of the patients were never screened for bladder abnormalities. Eight percent were never screened for renal malformations. In the majority of patients (79%), a PSARP was performed for the definitive reconstruction. - Conclusion - This collaborative effort provides a representative basis to estimate incidence of ARM types, to discuss differences and similarities in treatment, and health consequences throughout Europe.
Gesehen am 10.12.2020